The effect of chelating agents on synthesised nano-sized CoAl2O4 by thermal decomposition. (6th July 2010) - Tadjarodi, Azadeh; Aliakbari, Azam
Nano-sized CoAl2O4 spinel powders were synthesised by thermal decomposition with different chelating agents and surfactants [urea (U), citric acid (CA), sucrose (S), starch (St), poly (acrylic acid sodium salt) (PAS)]. Characterisation of result CoAl2O4 nanoparticles were performed by using X-ray diffractometer (XRD), scanning electron microscopy (SEM), energy disperse X-ray analysis (EDX), UV-Visible and FT-IR spectroscopy. The range size of result nanoparticles is 20-40 nm.